Benefits of Group Living Include Increased Feeding Efficiency and Lower Mass Loss during Desiccation in the Social and Inbreeding Spider Stegodyphus dumicola - Vanthournout, Bram; Greve, Michelle; Bruun, Anne; Bechsgaard, Jesper; Overgaard, Johannes; Bilde, Trine (Frontiers in Physiology, 2016)
Group living carries a price: it inherently entails increased competition for resources and reproduction, and may also be associated with mating among relatives, which carries costs of inbreeding. Nonetheless, group living and sociality is found in many animals, and understanding the direct and indirect benefits of cooperation that override the inherent costs remains a challenge in evolutionary ecology. Individuals in groups may benefit from more efficient management of energy or water reserves, for example in the form of reduced water or heat loss from groups of animals huddling, or through reduced energy demands afforded by shared participation in tasks. We investigated the putative benefits of group living in the permanently social spider Stegodyphus dumicola by comparing the effect of group size on standard metabolic rate, lipid/protein content as a body condition measure, feeding efficiency, per capita web investment and weight/water loss and survival during desiccation. Because energetic expenditure is temperature sensitive, some assays were performed under varying temperature conditions. We found that feeding efficiency increased with group size, and the rate of weight loss was higher in solitary individuals than in animals in groups of various sizes during desiccation. Interestingly, this was not translated into differences in survival or in standard metabolic rate. We did not detect any group size effects for other parameters, and group size effects did not co-vary with experimental temperature in a predictive manner. Both feeding efficiency and mass loss during desiccation are relevant ecological factors as the former results in lowered predator exposure time, and the latter benefits social spiders which occupy arid, hot environments.